2020
DOI: 10.1017/s0954579420000632
|View full text |Cite
|
Sign up to set email alerts
|

Pathways linking adverse environments to emerging adults’ substance abuse and depressive symptoms: A prospective analysis of rural African American men

Abstract: For African American emerging adult men, developmental challenges are evident in their escalating substance abuse and depressive symptoms; this is particularly true for men from low-resource communities. The present study tests a developmental model linking childhood adversity and contemporaneous contextual stressors to increases in emerging adults’ substance use and depressive symptoms, indirectly, via increases in defensive/hostile relational schemas and social developmental risk factors (e.g., risky peers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…A minority of studies (Kogan et al, 2021 ; Ross et al, 2019 ; van Assche et al, 2020 ; Wong et al, 2019 ) reported an a priori power analysis before data collection (fourth criterion). Proposed mediating variables were adequately defined by researchers in the majority of the studies, and valid measurements were utilized in most cases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A minority of studies (Kogan et al, 2021 ; Ross et al, 2019 ; van Assche et al, 2020 ; Wong et al, 2019 ) reported an a priori power analysis before data collection (fourth criterion). Proposed mediating variables were adequately defined by researchers in the majority of the studies, and valid measurements were utilized in most cases.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of included studies ( n = 25; 81%) explored factors that mediated or moderated the relationship between child adversity and depression; 12 studies (39%) investigated intervening variables in the relationship between child adversity and anxiety, and six studies (19%) examined mediators in the relationship between adversity in childhood and trauma. In some studies, the role of biological intervening variables was also tested (e.g., Kogan et al, 2021 ). These variables were outside the scope of the current review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We conducted an MLFA to develop an OXT methylation index (OXTmi) that reflects the characteristics of the representative probes in the promoter region [29].…”
Section: Maximum Likelihood Factor Analysis (Mlfa)mentioning
confidence: 99%